Increased Postural Sway Predicts Negative Symptom Progression in Youth at Ultrahigh Risk for Psychosis - Dean, Derek J. (Schizophr Res, 2015)
Impaired ability to maintain an upright posture may reflect impairment in the cerebellum, a critical structure for the fluid coordination of neural information, thought to be disrupted in psychosis. The current study utilized an instrumental measure of posture in individuals at ultrahigh risk (UHR) for psychosis (n=43) and healthy controls (n=44). Positive and negative symptoms were assessed twice over 12-months. Results showed that increased postural sway in the UHR group predicted changes in negative symptoms. This study provides an important prospective view on the relationship between cerebellar-sensitive behavior and integral symptoms, which until now has received limited biomarker research.